Growth, Spectral, Linear and Nonlinear Optical Characteristics of A Novel Organic L-Proline Adipate Single Crystals. (2019) - Indumathi, N.; Deepa, K.; Chinnasamy, E.; Suresh Kumar, D.; Madhavan, J.; Senthil, S.
Abstract: The growth and characterization of the L-Proline Adipate (LPA) nonlinear optical single crystals have been grown by slow evaporation technique at room temperature. The single crystal XRD illustrates the LPA corresponds to monoclinic system. The discrete functional groups exist in LPA were calculated by FTIR spectral investigation. The UV-VIS-NIR emits the optical properties for the grown LPA crystals. Several optical properties specifically Extinction coefficient, Reflectance, Linear refractive index were also determined. The calculated dielectric property of LPA was investigated by employing the dielectric studies. The Thermal behaviour of the LPA crystal has been found out by Thermal Gravimetric Analysis and Differential thermal Analysis. The SHG was characterized by utilizing the Kurtz Perry technique.